The urban question, the scale question and the border question: the Tacna-Arica border space (southern peru and northern chile) towards future - Valdebenito Tamborino, Felipe (2018)
I introduce an essay that diagnoses the urban, scale and border possibilities and challenges that are developing on the Tacna-Arica border space during the last decade; pointing out the importance of those issues towards the mutual future of Tacna and Arica cities. With this aim, I discuss the concepts of urban, scale, and border from a geographical “extended” point of view and, from there, I elaborate a personal propose to address the border case been studied: a Tacna-Arica border urbanization scale.